IMPLEMENTASI STRATEGI PEMASARAN SYARIAH DALAM KOPERASI SIMPAN PINJAM DI KOPPONTREN (AL-MASHDUQIAH) - Rofiatul Masyruroh; Siti Aisyah (IZZI: Jurnal Ekonomi Islam, 2021)
The focus of this study aims to analyze the implementation of marketing strategies in Islamic . This research method uses qualitative research methods using observation and interviews, data sources are managers, administrators, and employees. The results showed that the marketing strategy in the savings and loan cooperatives through door to door was carried out by the collection team.